“I’m not discriminating against you, but…”: Navigating Fertility Assistance as a Fat, Single Woman - Ioannoni, Kelsey (Atlantis)

(untitled) (Mount Saint Vincent University, 2024)
In this paper, I use an autoethnographic approach to explore the fertility processes I underwent and the difficulties I had in accessing fertility services in an effort to get pregnant as a fat single mother by choice. Here, I outline my experiences at two different fertility clinics, one of which denied me care based on my fatness. I reflect on the difficulties of accessing fertility services as a fat woman, and indeed how fat women are viewed as risky bodies to be deterred from motherhood. I conclude this paper by situating the joyous delivery of my son against the backdrop of being “high risk.”